NUTRIENT STOCKS IN FOUR STAGES OF A LOWLAND RAIN FOREST AT PASIRMAYANG, JAMBI, CENTRAL SUMATRA, - PAMUJI LESTARI (BIOTROPIA, 1998)
Studies of nutrient cycling of tropical forests should differentiate between dynamic stages of the forest. We studied the nutrient concentration (N, P, K, Ca and Mg) and phytomass of aboveground (living and non living parts) and belowground compartments (soil) in four dynamic stages, namely Building (Bl and B2), and Mature (Ml and M2) stages, for a lowland rain forest. Nutrient concentrations in various compartments differed between the dynamic stages. Bark contains higher nutrient concentration than wood parts, both in stems and branches. Leaves contain higher nutrient concentration than wood parts, both in litterfall and litter. The concentration of K in throughfall is the highest, Ca and Mg perform similar value. Throughfall exhibits lower nutrient concentration than open area rain water. The nutrient concentration of 10-20 cm is higher than in the 0-10 cm soil depth. The phytomass values are highly variable among tree parts, diameter classes and dynamic stages. The phytomass is generally the highest in M2 and significantly different from Bl ,Â  Ml and B2. The phytomass of leaves in litterfall and litter is higherÂ  than wood parts. More litterfall and litter are accumulated in mature than building phases. Key words : nutrient / phytomass / dynamics / rain / forest